Handbook of research on pedagogies and early intervention strategies for combatting socio-pathological behaviors - Buckley, Sheryl, 1959-; Babic, Ivana, 1973-; Kadum, Vladimir; Hmelak, Maja, 1982- (Information Science Reference, 2022)
"This book is intended to serve as a guide to the social pedagogy discipline for those involved in many levels who are dealing with different types of socio-pathological phenomena and problems in the theory and practice, and offering an in-depth theoretical framework and a primary emphasis on practice with applications to interdisciplinary educational environments"- Resumé vydavatel
Keywords: sociální pedagogika; behaviorální terapie; problémové děti; etopedie; social pedagogy; behavioral therapy; problem children; education of problem children